The evolution of artificial intelligence in foreign language teaching - Koliada, I. V.; Kostochka, I. (Університет Григорія Сковороди в Переяславі, 2026)
The article explores the historical development of artificial intelligence and its application in the educational field, with particular emphasis on foreign language teaching. The main stages of AI integration into education are analyzed, from early computer-assisted language learning to modern intelligent language learning systems. The study highlights the impact of artificial intelligence on teaching methodologies, assessment practices, and personalized language learning. Special attention is given to the role of AI technologies in higher education and digital language instruction.

У статті досліджено історичний розвиток штучного інтелекту та його застосування в освітній сфері з особливим акцентом на викладання іноземних мов. Проаналізовано основні етапи інтеграції штучного інтелекту в освіту – від ранніх форм комп’ютерно-асистованого навчання мов до сучасних інтелектуальних систем вивчення мов. У дослідженні висвітлено вплив штучного інтелекту на методики навчання, практики оцінювання та персоналізоване мовне навчання. Особливу увагу приділено ролі технологій штучного інтелекту у вищій освіті та цифровому мовному навчанні.
Keywords: artificial intelligence; education; foreign language teaching; educational technologies; computer-assisted language learning; personalized learning; штучний інтелект; освіта; викладання іноземних мов; освітні технології; комп'ютерно-асистоване навчання мов; персоналізоване навчання